Grouping of Books Type Based by Time Borrowing (months) Using Fuzzy C-Means Algorithm. (case Study: Surabaya Public Library) - Bachtiar Azhari; Rifki Fahrial Zainal; Rani Purbaningtyas (Fakultas Teknik Universitas Bhayangkara, 2017)
Book lending transactions are the main activities that take place in the Library. With the method of grouping, it willget what kind of books are most often borrowed. The method used is Fuzzy C-Means. This thesis discusses theapplication of Fuzzy C-Means method to classify book data based on lending per month and measure the effectivenessof the use of methods in the process. This application has been tested by producing 3 clusters and classify the time(month) where the frequency of borrowing done by visitors in the Library.